Artikel Peningkatan Hasil Belajar Materi Asmaul Husna Dengan Metode Make A Match - Yulizar Hajriandi (GHIROH, 2022)
One of the learning materials for Islamic Religious Education which is considered quite difficult is memorizing Asmaul Husna. This difficulty is because the ability to remember (memory) of each student is different. One strategy to deal with it is quite easy by applying a PAIKEM learning method (Active Innovative Creative Effective and Fun Learning) such as the make a match learning method (Looking for a Partner). This study aims to describe the results of increasing the memorization ability of Asmaul Husna by applying the Make a Match method for sixth grade elementary school students at Bintan Regency. This research is a classroom action research with two cycles. Student and teacher observation data were analyzed qualitatively with student and teacher activity observation sheets, and student learning outcomes data were analyzed quantitatively (description of learning outcomes). Based on the results of data analysis, it can be concluded that the application of the Make a Match method can improve learning outcomes of Islamic Religious Education on Asmaul Husna memorizing material for sixth grade elementary school students. Improved student learning outcomes can be seen both in the learning process such as activeness and enthusiasm of students in learning, and can be seen in the results of the post-test of students at the end of the learning cycle.